A Decentralized Control Strategy for High Density Material Flow Systems with Automated Guided Vehicles - Schwab, Melanie (Wissenschaftliche Berichte des Instituts für Fördertechnik und Logistiksysteme des Karlsruher Instituts für Technologie, 2015)
This work presents a universal decentralized control strategy for grid-based high-density material flow systems with automated guided vehicles and gives insights into the system behavior as well as the solution quality.